Violência e acidentes : caracterização das vítimas atendidas em Sergipe. - Vaez, Andréia Centenaro (2011)
Trauma caused by accidents and violence is a serious public health problem in Brazil, not only by its magnitude but also because victims are young people in working age. This study had proposed to characterize victims of accidents and violence assisted in an emergency unit in the State of Sergipe. This is a descriptive, prospective cross-sectional based on quantitative approach research. The study was conducted in a public hospital from Aracaju city, which is a reference center in assisting trauma victims in the State of Sergipe. Study sample was purposive, consisting of 504 victims of accidents or violence in the State of Sergipe, assisted trough November, 2010, aging 12 or higher that. Results showed that the trauma victims had an average age of 31.28 years old, most of them were male, single, coming the area called "Grande Aracaju", having an average schooling of 6.64 years and they were involved in wage-earning activity. The man trauma mechanism was traffic accident, with alcohol abuse and illicit drugs reports, lacerations blunts on the upper and lower limbs, followed by lesions in the region of face, head and neck. The initial evaluation at hospital evidenced that for most victims trauma was considered mild, scoring from 13 to 15 in Glasgow Coma Scale, Revised Trauma Score, and unaltered cardiac and respiratory rates was inalterad, with mild intensity pain reports. Immobilization and peripheral venous access were the most frequent basic and advanced support procedures performed in pre-hospital care. Bandages and medication were prevalent within the emergency room. Regarding assistance, the assistance's outcome was the discharge from the emergency room. There had been statistically significant association between traffic accidents and violence regarding schooling, income, occupation and provenance. There was also association of falls to age, schooling, income, gender, marital status and disability reports. Regarding associations between risk factors (reports of drinking of alcoholic beverages, drug consumption, non-use of personal protective equipment and physical, visual, auditory or mental disabilities) and accidents and violence there was also significance